Cytotoxic Efficiency of Human CD8+ T Cell Memory Subtypes - Knörck, Arne; Schäfer, Gertrud; Alansary, Dalia; Richter, Josephine; Thurner, Lorenz; Hoth, Markus; Schwarz, Eva C. (Frontiers in Immunology, 2022)
Immunological memory is important to protect humans against recurring diseases. Memory CD8+ T cells are required for quick expansion into effector cells but also provide immediate cytotoxicity against their targets. Whereas many functions of the two main cytotoxic subtypes, effector memory CD8+ T cells (TEM) and central memory CD8+ T cells (TCM), are well defined, single TEM and TCM cell cytotoxicity has not been quantified. To quantify cytotoxic efficiency of TEM and TCM, we developed a FRET-based single cell fluorescent assay with NALM6 target cells which allows analysis of target cell apoptosis, secondary necrosis following apoptosis, and primary necrosis after TEM- or TCM-target cell contact. Both, single cell and population cytotoxicity assays reveal a higher cytotoxic efficiency of TEM compared to TCM, as quantified by target cell apoptosis and secondary necrosis. While perforin, granzyme B, FasL, but not TRAIL expression are higher in TEM compared to TCM, the higher cytotoxic efficiency of TEM compared to TCM is a result of higher perforin expression. Both, TEM and TCM need the same time to find their targets, however contact time between CTL and target, time to induce apoptosis, and time to induce secondary necrosis are all shorter for TEM. Defining and quantifying single TEM and TCM cytotoxicity and the respective mechanisms is important to optimize future subset-based immune therapies.